Rede de tags para recuperação da informação no contexto da Representação Iterativa - Santarem Segundo, José Eduardo [UNESP]; Vidotti, Silvana Aparecida Borsetti Gregorio (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2011)
Information retrieval is a recurrent subject in search of information science. This kind of study aim to improve results in both searches on the Web and in various other digital information environment. In this context, the Iterative Representation model suggested for digital repositories, appears as a differential that changes the paradigm of self-archiving of digital objects, creating a concept of relationship between terms that link the user thought the material deposited in the digital environment. The links effect by the Iterative Representation aided Assisted Folksonomy generate a shaped structure that connects networks, vertically and horizontally, the objects deposited, relying on some kind of structure for representing knowledge of specialty areas and therefore, creating an information network based on knowledge of users. The network of information created, called the network of tags is dynamic and effective a different model of information retrieval and study of digital information repositories.Keywords Digital Repositories; Iterative Representation; Folksonomy; Folksonomy Assisted; Semantic Web; Network Tags.

A recuperação da informação tem sido abordada constantemente dentro da Ciência da Informação, gerando e incentivando vários estudos que levem a melhorar os resultados em buscas tanto na Web como em vários outros ambientes digitais informacionais. Neste contexto a Representação Iterativa, modelo sugerido para repositórios digitais, aparece como um diferencial que altera o paradigma do auto-arquivamento de objetos digitais criando um conceito de relacionamento entre os termos que ligam o pensamento do usuário ao material depositado no ambiente digital. As ligações efetivadas pela Representação Iterativa com auxílio da Folksonomia Assistida geram uma estrutura em formato de redes que conecta de forma vertical e horizontal os objetos depositados, apoiando-se em algum tipo de estrutura de representação do conhecimento das áreas de especialidades e portanto criando uma rede de informações baseada no conhecimento dos usuários. A rede de informações criada, chamada de rede de tags, é dinâmica e efetiva um modelo diferente de recuperação da informação e estudo dos repositórios digitais informacionais.
Network tags for information retrieval in the context of Iterative Representation
Keywords: Repositórios digitais; Representação Iterativa; Folksonomia; Folksonomia Assistida; Rede de Tags